CEFDITOREN IN THE TREATMENT OF PURULENT RINOSINUSITIS - G. N. Nikiforova; V. M. Svistushkin; D. M. Pshonkina (Медицинский совет, 2017)
Rhinosinusitis is one of the most common human nosologies. Treatment of acute forms of rhinosinusitis should be comprehensive and directed, first of all, to the eradication of the infectious agent, as well as to restore aeration of the sinuses and drainage function of the anastomosis. With the development of bacterial inflammation, it is necessary to decide the feasibility of systemic antimicrobial therapy. With starting empirical therapy, the drug of choice is amoxicillin, but at the risk of antibiotic resistance, as well as the ineffectiveness of starting therapy, it is recommended to use protected aminopenicillins or cephditoren. Spectraceph (cephditoren) is effective in the therapy of patients acute purulent rhinosinusitis, including with prolonged, recurrent course.